2022
DOI: 10.1177/10760296221132556
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban Versus Enoxaparin for Thromboprophylaxis After major Gynecological Cancer Surgery: The VALERIA Trial

Abstract: Direct oral anticoagulants (DOACs) for venous thromboembolism (VTE) prevention after major gynecological cancer surgery might be an alternative to parenteral low-molecular-weight heparin (LMWH). Patients undergoing major gynecological cancer surgery were randomized at hospital discharge to receive rivaroxaban 10 mg once daily or enoxaparin 40 mg once daily for 30 days. The primary efficacy outcome was a combination of symptomatic VTE and VTE-related death or asymptomatic VTE at day 30. The primary safety outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…Our study is essentially similar to Longo de Oliveira et al 26 Oliveira et al found no significant difference between rivaroxaban and LMWH in preventing postoperative VTE and bleeding (either major or minor) in patients with gynecologic oncology cancer. However, in this study, minor bleeding was higher in both groups than in the study by Oliveira et al It was higher in the rivaroxaban group than in the LMWH group.…”
Section: Discussionsupporting
confidence: 90%
“…Our study is essentially similar to Longo de Oliveira et al 26 Oliveira et al found no significant difference between rivaroxaban and LMWH in preventing postoperative VTE and bleeding (either major or minor) in patients with gynecologic oncology cancer. However, in this study, minor bleeding was higher in both groups than in the study by Oliveira et al It was higher in the rivaroxaban group than in the LMWH group.…”
Section: Discussionsupporting
confidence: 90%
“…The VALERIA study, another recent prospective, randomized trial comparing 30-day rivaroxaban versus enoxaparin in VTE prophylaxis after major gynecological cancer surgery, reported that symptomatic VTE was 2.63% versus 1.75% (relative risk, 1.50; 95% CI, 0.25–8.80; P = .6535) and major/clinically relevant nonmajor bleeding was 0% versus 2.63% (hazard ratio, 0.14; 95% CI, 0.007–2.73; P = .1963). 23 The authors concluded that their results support the hypothesis that DOACs might be an attractive alternative strategy to LMWH to prevent VTE after major gynecological cancer surgery. As regards the current study, the incidence of postoperative symptomatic VTE was 0.6% in Period 2 and 0.3% in Period 3 ( Table 3 ), both of which were lower than those by LMWH and DOAC in the two trials.…”
Section: Discussionmentioning
confidence: 68%
“…As regards the current study, the incidence of postoperative symptomatic VTE was 0.6% in Period 2 and 0.3% in Period 3 ( Table 3 ), both of which were lower than those by LMWH and DOAC in the two trials. 21 , 23 Although the prophylactic effect of the measures in Period 1 is undetermined due to the absence of publications on the postoperative symptomatic VTE incidences without prophylaxis, it is possible that our preoperative VTE screening contributes to effective prevention of postoperative symptomatic VTE in all the study periods. Furthermore, none of the patients with preoperative VTE who switched to DOAC in Period 3 developed symptomatic VTE with no increase in Grade ≥3 postoperative hemorrhage ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…32 A further study has since terminated early (due to lower than anticipated event rates), demonstrating similar VTE and bleeding rates in women receiving rivaroxaban 10 mg daily compared to enoxaparin 40 mg daily for 30 days from hospital discharge following gynaecological cancer surgery. 71…”
Section: Direct Oral Anticoagulants and Cancer Surgerymentioning
confidence: 99%
“…These studies drove the recent recommendation from the American Society of Clinical Oncology to include rivaroxaban and apixaban as an option for extended thromboprophylaxis following cancer surgery, with a caveat that the level of evidence remains low due to variation in timing of DOAC initiation, duration of initial heparin lead‐in, and in both type of cancer, and surgery performed 32 . A further study has since terminated early (due to lower than anticipated event rates), demonstrating similar VTE and bleeding rates in women receiving rivaroxaban 10 mg daily compared to enoxaparin 40 mg daily for 30 days from hospital discharge following gynaecological cancer surgery 71 …”
Section: Pharmacological Thromboprophylaxismentioning
confidence: 99%